HIV birth testing and linkage to care for HIV-infected infants. (24th August 2017) - Jean-Philippe, Patrick; Spiegel, Hans; Gnanashanmugam, Devasena; Fitzgibbon, Joseph; D'Souza, Patricia; Crawford, Keith W.; Jayashankar, Lakshmi; Bacon, Melanie C.; Essajee, Shaffiq M.; Aldrovandi, Grace M.; Cotton, Mark; Abrams, Elaine J.
Abstract : N/A: On 5–6 May 2016, the division of AIDS of the National Institute of Allergy and Infectious Diseases convened a workshop on 'HIV Birth Testing and Linkage to Care for HIV Infected Infants.' The goal of the workshop was to evaluate birth testing for early infant diagnosis (EID) of HIV, delineate technological resources for advancing a point-of-care (POC) HIV test implementable at birth and chart out the implementation hurdles for initiating early antiretroviral therapy to HIV-infected infants diagnosed at birth. The workshop addressed research and regulatory needs involved in the optimization of POC EID testing and challenges associated with implementation of EID, focusing on testing at birth. Scientific gaps and areas of intervention to accelerate and scale-up EID initiatives and birth testing were identified. These include discussion of the evidence supporting an early mortality peak among HIV-infected infant and justifying a role for birth HIV testing, including POC testing; evaluation of the current POC EID technology pipeline and test performance characteristics required for effective programmatic uptake; mathematical modeling of different testing scenarios and solutions with inclusion of birth testing; the adoption of setting-specific EID testing algorithms to achieve efficient linkage to care including early antiretroviral therapy initiation; the development of appropriate quality assurance programs to ensure accuracy of test results and enable sustainability of the testing program. Addressing these gaps and answering these challenges will be important in helping improve outcomes for HIV-infected infants and accelerate achieving the Joint United Nations Program for HIV and AIDS 90–90–90 targets in children.